2022
DOI: 10.3389/fphar.2022.818127
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Targets AKT1 to Inhibit Inflammasome Activation in Cardiomyocytes Under Acute Sympathetic Stress

Abstract: Resveratrol shows promizing anti-inflammatory effects in recent clinical trials, however its function in cardiovascular patients remains conflicting, suggesting there may be new mechanisms underlying its cardioprotective activity. Acute sympathetic stress induces early activation of the NLR family, pyrin domain containing 3 (NLRP3) inflammasome in cardiomyocytes as a critical step for triggering cardiac inflammation. Thus, this study explored targets of resveratrol activity involved in the inhibition of early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Resveratrol formed four hydrogen bonds with Asn54 and Thr82 in the PH domain and Gln203 and Ser205 in the kinase domain. Likewise, a previous study reported that resveratrol could bind to Akt-1 with an allosteric site [ 18 ]. RD2 formed four hydrogen bonds with Asn54, Gln79 (2 bonds) in the PH domain, and Ser205 in the kinase domain.…”
Section: Resultsmentioning
confidence: 99%
“…Resveratrol formed four hydrogen bonds with Asn54 and Thr82 in the PH domain and Gln203 and Ser205 in the kinase domain. Likewise, a previous study reported that resveratrol could bind to Akt-1 with an allosteric site [ 18 ]. RD2 formed four hydrogen bonds with Asn54, Gln79 (2 bonds) in the PH domain, and Ser205 in the kinase domain.…”
Section: Resultsmentioning
confidence: 99%
“…AKT1 may inhibit activation of NLRP3 inflammatory corpuscles in myocardial cells and is an important target for intervention in inflammation activation and initiation. [46] TP53 may inhibit the transcription of vascular endothelial growth factor, and therefore, prevent AS. [47] Several studies show that heat shock protein 90 (HSP90) was the target of anti-AS and could resist inflammation, [48][49][50][51] oxidative stress, and smooth muscle proliferation, and regulate the endothelial function by inhibiting the expression of HSP90.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that resveratrol targeting AKT1 inhibited inflammatory vesicle activation in cardiomyocytes under sympathetic stress, inhibited β-adrenergic receptor-mediated NLRP3 inflammatory vesicle activation in cardiomyocytes and mouse hearts, and the resulting cardiac inflammation. [ 41 ] IL-6 and VEGFA are closely related to the progression of cardiac hypertrophy and coronary artery disease, while VEGFA is widely distributed in the brain, VEGFA is widely distributed in the brain, heart, and other tissue cells, and has an important regulatory role in angiogenesis and atherosclerosis. [ 42 ] Studies have shown that MSCs can reduce inflammation in the heart and lungs through TNF signaling.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that resveratrol targeting AKT1 inhibited inflammatory vesicle activation in cardiomyocytes under sympathetic stress, inhibited β-adrenergic receptor-mediated NLRP3 inflammatory vesicle activation in cardiomyocytes and mouse hearts, and the resulting cardiac inflammation. [41] Figure 2. The intersection of Datura metel sinus bradycardia targets.…”
Section: Discussionmentioning
confidence: 99%